Beyond the box : B.F. Skinner's technology of behavior from laboratory to life, 1950s-1970s - Rutherford, Alexandra, 1971- (Book collections on Project MUSE., 2009)
Beyond the Box is the first full-length study of the ways in which Skinner's ideas left the laboratory to become part of the post-war public's everyday lives, and chronicles both the enthusiasm and caution with which this process was received.